ELPylated haemagglutinins produced in tobacco plants induce potentially neutralizing antibodies against H5N1 viruses in mice. Issue 5 (11th February 2013) - Phan, Hoang T.; Pohl, Julia; Floss, Doreen M.; Rabenstein, Frank; Veits, Jutta; Le, Binh T.; Chu, Ha H.; Hause, Gerd; Mettenleiter, Thomas; Conrad, Udo
Summary Reducing the cost of vaccine production is a key priority for veterinary research, and the possibility of heterologously expressing antigen in plants provides a particularly attractive means of achieving this. Here, we report the expression of the avian influenza virus haemagglutinin (AIV HA) in tobacco, both as a monomer and as a trimer in its native and its ELPylated form. We firstly presented evidence to produce stabilized trimers of soluble HA in plants. ELPylation of these trimers does not influence the trimerization. Strong expression enhancement in planta caused by ELPylation was demonstrated for trimerized H5‐ELP. ELPylated trimers could be purified by a membrane‐based inverse transition cycling procedure with the potential of successful scale‐up. The trimeric form of AIV HA was found to enhance the HA‐specific immune response compared with the monomeric form. Plant‐derived AIV HA trimers elicited potentially neutralizing antibodies interacting with both homologous virus‐like particles from plants and heterologous inactivated AIV. ELPylation did not influence the functionality and the antigenicity of the stabilized H5 trimers. These data allow further developments including scale‐up of production, purification and virus challenge experiments with the final goal to achieve suitable technologies for efficient avian flu vaccine production.